2019
DOI: 10.1051/e3sconf/20198001004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of factors affecting sustainable development of renewable energy sources in transport

Abstract: At present motor transport is one of the key components of the formation of a long-term policy of sustainable economic development. Analysis of the structure of energy consumption in motor transport is necessary for better understanding of the factors that affect the increase in the share of renewable energy sources in transport and the effectiveness of specific support measures for the transition to vehicles with minimal or no greenhouse gas emissions. Models of pooled regression, regression with random and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Regarding the three disclosure scores of ESG, it is found that environmental disclosure has a mean value of 15.66 with a maximum score of 83.94 and minimum of 0. Eder, et al [31]. It also has value of C. V. as high as 138.4%.…”
Section: Methodsmentioning
confidence: 94%
“…Regarding the three disclosure scores of ESG, it is found that environmental disclosure has a mean value of 15.66 with a maximum score of 83.94 and minimum of 0. Eder, et al [31]. It also has value of C. V. as high as 138.4%.…”
Section: Methodsmentioning
confidence: 94%